Academic Burnout Among Students During the COVID 19 Pandemic: a Gender-Based Analysis - Fatma Nofriza; Dony Darma Sagita; Fitniwilis Fitniwilis; Vriesthia Meilyawati; Ahmad Yunus (Ta'dib, 2022)
Academic burnout among FKIP UHAMKA students will be analyzed based on gender. A descriptive approach is utilized in the quantitative research methodology. A sample of 307 students was chosen from the 6,544 total pupils who participated in the research. According to the study's findings, academic burnout can be classified according to a person's gender. The researchers discovered that male students fell into the low category, scoring 75% in sub-variable exhaustions, 61% in cynicism, and 50% in inefficacy. Additionally, the majority of female students fall into the low category, with percentage values in the subvariables for weariness (76%), cynicism (63%), and inefficacy (64%) all falling into the low range. Thus, it can be said that both male and female students at FKIP UHAMKA have low levels of academic burnout.